Wasiat Wajibah Kategori Ahli Waris Pengganti Dalam Hukum Waris Di Indonesia - Basit Misbachul Fitri, Abdul; Fadhilatur Rofiah, Ayu (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2021)
A mandatory will is a will whose implementation is not influenced or does not depend on the will or will of the deceased and must be implemented. The provisions of the mandatory will is the result of the ijtihad of the scholars in interpreting verse 180 of surah al-Baqarah. Some Uama' allow it and some forbid it. Based on the hadith about the will, the hadith from Thabit Ibn Anas that the Prophet SAW said: to Abu Talhah,